Plasma microRNA profiling predicts HIV-associated neurocognitive disorder. (24th August 2016) - Asahchop, Eugene L.; Akinwumi, Segun M.; Branton, William G.; Fujiwara, Esther; Gill, M. John; Power, Christopher
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: HIV-associated neurocognitive disorder (HAND) is a common neurological disorder among HIV-infected patients despite the availability of combination antiretroviral therapy. Host-encoded microRNAs (miRNA) regulate both host and viral gene expression contributing to HAND pathogenesis and can also serve as disease biomarkers. Herein, plasma miRNA profiles were investigated in HIV/AIDS patients with HAND. Methods: Discovery and Validation Cohorts comprising HIV/AIDS patients were studied that included patients with and without HAND (non-HAND). Plasma miRNA levels were measured by array hybridization and verified by quantitative real-time reverse transcriptase PCR (qRT-PCR). Multiple bioinformatic and biostatistical analyses were applied to the data from each cohort. Results: Expression analyses identified nine miRNAs in the Discovery Cohort (HAND, n = 22; non-HAND, n = 25) with increased levels (≥two-fold) in the HAND group compared with the non-HAND group ( P < 0.05). In the Validation Cohort (HAND, n = 12; non-HAND, n = 12) upregulation (≥two-fold) of three miRNAs (miR-3665, miR-4516 and miR-4707–5p) was observed in the HAND group that were also increased in the Discovery Cohort's HAND patients, which were verified subsequently by qRT-PCR. Receiver-operating characteristic curve analyses for the three miRNAs also pointed to the diagnosis of HAND (area under curve, 0.87, P < 0.005). Bioinformatics tools predicted that all three miRNAs targeted sequences of genes implicated in neural development, cell death, inflammation, cell signalling and cytokine functions. Conclusion: Differentially expressed plasma-derived miRNAs were detected in HIV/AIDS patients with HAND that were conserved across different patient cohorts and laboratory methods. Plasma-derived miRNAs might represent biomarkers for HAND and also provide insights into disease mechanisms.